The Effectiveness of Self-Instructional Video vs. Classroom Teaching Method on Focused Assessment With Sonography in Trauma Among House Officers in University Hospital - Isa, Mohd Hisham; Lim, Kristina; Jaafar, Mohd Johar; Mohd Saiboon, Ismail (Frontiers in Surgery, 2021)
Abstract Abstract Background: The aim of this study was to compare the effectiveness of self-instructional-video (SIV) and classroom training method (CTM) in learning Focus-Assessment with Sonography-in-Trauma (FAST) among house officers (HO). Method: A randomized controlled study involving house officers working in the university hospital in Malaysia was conducted where participants were randomized into SIV group (intervention) and CTM group (control). Each group had to undergo a four-hour hands-on training. The intervention group has undergone self-training using the video material without any facilitation while the control group received lecture and hands-on training with facilitators. Participants’ performance was assessed using a validated Objective Structured Clinical Examination checklist for landmark identification and interpretation of images generated. Learning preference and confidence level were also assessed. Result: A total of 33 HO were enrolled in this study. Marks obtained in image acquisition by the intervention and control were 25.3(SD 5.3) and 25.6(SD2.3) p>0.05, respectively. While in image interpretation, the mean score for the intervention and control group was 10.3 (SD 1.7) and 9.8 (SD 1.7) p>0.05, respectively. Overall performance assessment, showed the intervention group obtained 35.6 (SD 5.9) compared to control 35.3 (SD 3.4), p >0.05. Based on pre-specified determinant these scores difference falls within the 10% of non-inferiority margin. The absolute difference between both groups was 0.3 (CI= -3.75 to 3.21, p=0.871), which proves non-inferiority but not superiority. In terms of learning preference and confidence to perform FAST, most of the participants preferred the control group approach. Conclusion: The SIV method is as effective as the CTM for learning FAST among the house officers and served as an alternative to classroom teaching. However, this technique needs improvement in promoting their confidence and preference. Perhaps incorporating a feedback session after going through the SIV would improve the confidence.